Chinese FDI in the United States is taking off: How to maximize its benefits? - Thilo Hanemann; Daniel H. Rosen (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2011)
China's outward foreign direct investment (OFDI) grew rapidly in the past decade, but flows to developed economies have been limited. Now China's direct investment flows to the United States are poised to rise substantially. This new trend offers tremendous opportunities for the U. S., provided policymakers take steps to keep the investment environment open and utilize China's new interest productively.
Keywords: 330